Studies on compatibility of biorational insecticides with fungicides against tobacco caterpillar, Spodoptera litura Fabricius on tobacco - Sailaja, B; ., Jayasekharan; Sreedhar, U; Rao, G Raghupathi (Indian Journal of Plant Protection, 2020)
Studies were conducted to assess the physical, chemical and biological compatibility of new insecticides with fungicides against tobacco caterpillar, Spodoptera litura Fabricius. Emamectin benzoate 5 SG @ 0.0025 % in combination with copper oxy chloride 50 WP @ 0.2 % and azoxystrobin 23 SC @ 0.1 % recorded 100 and 96.43 % mortality within 48 hours after treatment. Spinosad 48 SC @ 0.012 % and its combination with test fungicides recorded less than 85 % mortality. Insect growth regulators, lufenuron 5.4 EC @ 0.006 % and novaluron 10 EC @ 0.01 % in combination with various fungicides also recorded reduced mortality. Hence, it is better to apply the insecticides and fungicides used in the study separately barring the combinations of emamectin benzoate 5 SG @ 0.0025 % with copper oxy chloride 50 WP @ 0.2 % and azoxystrobin 23 SC @ 0.1 % .